Creative (and cultural) industry entrepreneurship in the 21st century. Volume 18, part B, - Hill, Inge; Elias, Sara R. S. T. A.; Dobson, Stephen; Jones, Paul (Contemporary issues in entrepreneurship research ;, 2024)
Creative and cultural industries are growing in almost every nation around the world and over the last two decades have contributed to global, national, and local economies significantly. More recently, policy makers and those who start these creative businesses have demonstrated a greater interest in how creative entrepreneurs create, sustain and market their services and products. And how contexts influence their 'doing business' is of increasing importance. Both volumes of Creative (and Cultural) Industry Entrepreneurship in the 21st Century map and elucidate the adaptations and challenges faced by the creative professionals and the entrepreneurial solutions they have co-developed. Illuminating how contexts and recent socio-economic disruptive challenges influence how value is created and maintained from start-up to growth and exit, the chapter authors take a fresh look at creative micro-businesses and SMEs, the processes leading to their formation, developments and their founders. This volume 2 adds a focus on how creative ventures could contribute to economic development and the challenges policy makers face. Contemporary Issues in Entrepreneurship Research is an official book series of the Institute for Small Business and Entrepreneurship (ISBE). Each volume is designed around a specific theme of importance to the entrepreneurship and small business community with articles collectively exploring and developing theory and practice in the field.